2021
DOI: 10.1186/s12870-021-03275-0
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant gene expression analysis and evaluation of total phenol content and oxygen-scavenging system in tea accessions under normal and drought stress conditions

Abstract: Background Abiotic and biotic stresses induce oxidative processes in plant cells that this process starts with the production of ROSs which cause damage to the proteins. Therefore, plants have increased their antioxidant activity to defend against this oxidative stress to be able to handle stress better. In this research, 14 different tea accessions in a randomized complete block design with two replications were evaluated in two normal and drought stress conditions, and their antioxidant activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 63 publications
3
11
0
Order By: Relevance
“…In our study, five differentially expressed DHAR genes were identified and were shown to assist plants in producing ascorbic acid to enhance their antioxidant capacity. SOD, POD, and CAT enzymes are also important antioxidant enzymes for free radical scavenging in plants, and the genes regulating these enzymes were also differentially expressed in our study (Rahimi et al, 2021). Two SOD genes in our study were upregulated in T2, but most of the 10 CAT genes were downregulated in T2.…”
Section: Key Pathways and Drought Tolerance-related Genes Under Droug...supporting
confidence: 53%
“…In our study, five differentially expressed DHAR genes were identified and were shown to assist plants in producing ascorbic acid to enhance their antioxidant capacity. SOD, POD, and CAT enzymes are also important antioxidant enzymes for free radical scavenging in plants, and the genes regulating these enzymes were also differentially expressed in our study (Rahimi et al, 2021). Two SOD genes in our study were upregulated in T2, but most of the 10 CAT genes were downregulated in T2.…”
Section: Key Pathways and Drought Tolerance-related Genes Under Droug...supporting
confidence: 53%
“…•− contents in FD and HJ1 under nitrogen treatments(Figure 2), which are consistent with our previous study as well [7]. At the same time, the up-regulation of the relative expressions of these genes (CsSOD, CsPOD, CsCAT, CsAPX) was directly involved in the increased enzyme activities [17,47,49]. Furthermore, as one of the most important antioxidants in plant tissues, GSH/GSSG is essential in maintaining redox homeostasis [50,51].…”
Section: Discussionsupporting
confidence: 90%
“…Plants respond to biotic and abiotic stresses with a serials of physiological and biochemical responses [16,17]. As a typical abiotic stress, nitrogen stress can induce plant growth inhibition and serious morphological, metabolic and physiological abnormalities [18].…”
Section: Introductionmentioning
confidence: 99%
“…Plants can integrate different stress signals and improve their chances of survival by inducing stomatal responses and the production of reactive oxygen species (ROS) and hormones ( Zhao et al, 2022 ). Oxygen-scavenging system can be used as a descriptor for identifying drought-tolerant accessions ( Rahimi et al, 2021 ). The analysis of transcriptome results also found that moderate drought had a great impact on the expression of Pro-, SOD-, and POD-related genes in tea roots.…”
Section: Discussionmentioning
confidence: 99%